Electromyographic activity of the vastus medialis and gastrocnemius implicates a slow stretch-shortening cycle during rowing in the field - Held, S.; Siebert, T.; Donath, L. (Scientific Reports, 2020)
The consideration of the temporal and electromyographic (EMG) characteristics of stretch-shortening cycles (SSC) are crucial for the conceptualization of discipline-specific testing and training. Since leg muscles are first stretched (eccentric) and then contracted (concentric) during rowing, it can be assumed that the entire muscle tendon complex performs a SSC. Thus, it should be elucidated whether the rowing cycle can be attributed to either a slow or fast SSC. Therefore, EMG of the vastus medialis and gastrocnemius were captured (n=10, 22.8±3.1 years, 190±6 cm, 82.1±9.8 kg) during (single scull) rowing and subsequently compared to typical slow (countermovement jump, CMJ) and fast (drop jump, DJ) SSCs. The elapsed time between the EMG onset and the start of the eccentric phase was monitored. The pre-activation phase (PRE, before the start of the eccentric phase) and the reflex-induced activation phase (RIA 30-120 ms after the start of the eccentric phase) have been classified. Notable muscular activity was observed during DJ before the start of the eccentric phase (PRE) as well as during RIA. In contrast, neither CMJ nor rowing revealed any EMG-activity in these two phases. Interestingly, CMJ and race-specific rowing showed an EMG-onset during the eccentric phase. We conclude that rowing is more attributable to a slow SSC and implies that fast SSC does not reflect discipline specific muscle action and could hamper rowing-performance-enhancement.